Modulation of Wnt/Beta-Catenin Pathway by Major Dietary Phytochemicals Against Breast Cancer Development - Noah Lieb; Annalisa Tran; Martha Torres; Ajay Bommareddy (Biology)
Breast cancer is one of the most commonly diagnosed cancers and is the second leading cause of cancer-related deaths among women in the United States. Despite a decrease in mortality associated with breast cancer, there has been a steady increase in its incidence. Development of the mammary gland is normally regulated by such pathways including Wnt, Hedgehog, estrogen and Notch signaling. However, the deregulation of these pathways gives rise to tumor development, and upregulated Wnt activity along with high levels of beta-catenin is correlated with poor prognosis of breast cancer. In addition, beta-catenin-dependent Wnt signaling is enriched in triple-negative breast cancers and is associated with reduced overall survival in breast cancer patients. Various studies have investigated the ability of naturally occurring plant-based agents to reduce incidence and morbidity of breast cancer by regulating critical cell survival pathways to reverse or inhibit the occurrence of clinical disease. The present review focuses on summarizing the role of commonly consumed dietary phytochemicals and their role in regulating Wnt/β-catenin pathway against the development of breast cancer.